James Moffett’s Lit Crit and Holy Writ - Charles Suhor (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
In one of Moffett's final presentations, he traced parallels between literary criticism and the study of scripture from various traditions. He explained the development of his Points of View spectrum as a response to his high school teaching experiences and presented an updated version of the spectrum.